SATELLITE-BASED MULTITEMPORAL CHANGE DETECTION IN IGNEADA FLOODED FORESTS - ALIYE GONCA BOZKAYA; FILIZ BEKTAS BALCIK; CIGDEM GOKSEL; AHMET OZGUR DOGRU; NESIBE NECLA ULUGTEKIN; SEVAL SOZEN (Revue Roumaine de Géographie)
Monitoring land use/land cover changes is a very important component for sustainable management of sensitive regions. Because of their ecological, biological, environmental and economic importance, Igneada flooded (longos) forests have a multiple role in the landscape. This study is conducted to detect and monitor land use and land cover changes of Igneada region using multi-temporal remotely sensed data. For this purpose, Landsat 5 TM satellite data were used, including four scenes acquired from 1984 to 2010. Change detection methodology of land use/land cover has four main stages: 1) Preprocessing of satellite images, 2) Classifying images using maximum likelihood method, 3) Accuracy assessment of the classification, 4) Comparing classified images in GIS environment and 5) Change detection.